Process for preparing powdery anhydrous accelerator through synergistic resource treatment of organic waste sulfuric acid and aluminum ash
By synergistically treating organic waste sulfuric acid and aluminum ash to generate anhydrous quick-setting agent, the resource waste and safety risks when aluminum ash and waste sulfuric acid are treated separately are solved, and efficient resource utilization and economic benefits are achieved.
Patent Information
- Application Number
- CN202511085307.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-08-04
AI Technical Summary
In the existing technology, when aluminum ash and waste sulfuric acid are treated separately, there are problems such as resource waste, safety risks, environmental risks, high energy consumption, and low product added value, making it difficult to achieve large-scale mass production and resource utilization.
Through the coordinated treatment of organic waste sulfuric acid and aluminum ash, including aluminum extraction from aluminum ash, denitrification and desalination, acidity adjustment of waste sulfuric acid, high-temperature calcination and calcination waste gas treatment, anhydrous accelerating setting agent is generated, and aluminum sulfate and other compounds are generated by high-temperature reaction. The waste gas is treated through multi-stage absorption to achieve efficient utilization of resources and anhydrous treatment.
The coordinated resource utilization of aluminum ash and waste sulfuric acid is achieved to generate anhydrous accelerating setting agent with market value, which reduces energy consumption, improves resource recovery rate and product added value, and achieves zero emission and significant economic benefits.
Smart Images

Figure CN120647194A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of industrial environmental protection technology, and in particular relates to a process for preparing a powdered anhydrous quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash. Background Art
[0002] Currently, waste sulfuric acid is typically classified into high-concentration and low-concentration waste sulfuric acid based on its concentration; it can also be further divided into high-organic waste sulfuric acid and low-organic waste sulfuric acid based on its organic matter content. Aluminum ash is a solid waste residue generated during the industrial smelting and processing of aluminum. It is divided into primary and secondary aluminum ash based on its source and metallic aluminum content. Aluminum ash is a hazardous waste because it contains active substances and a high total aluminum content, resulting in high thermal energy and aluminum value. Accelerators are classified as alkaline and acidic based on their acidity and alkalinity; and as anhydrous, liquid, and crystallized water based on their water content. Generally, in industrial practice, waste sulfuric acid and aluminum ash are treated separately, but this separate treatment process presents varying degrees of problems.
[0003] Regarding the disposal of aluminum ash, there are issues such as hazardous waste properties, waste of resources, safety risks, environmental risks, insignificant reduction in treatment, and low aluminum recovery rate. The commonly used pretreatment methods for aluminum extraction, acid dissolution, alkali dissolution, and calcination all have insignificant reduction. In industrial production, there are problems such as how to safely control hydrogen and ammonia, how to achieve large-scale mass production, and the economic benefits are not outstanding. In the process of industrial implementation, it is mainly reflected in the following aspects: ① The problem of safe handling of harmful substances (hydrogen, fluorine, chlorine, nitrogen, salt, etc.), especially the risk of hydrogen deflagration and explosion, which has high requirements for equipment and reaction rate. The safe and effective use of these elements in industrialization restricts large-scale mass production; ② Low value-added products: mainstream processes such as the preparation of aluminum sulfate, polyaluminum chloride, cement additives, and inert aluminum materials (acids ③ The utilization rate of alumina in aluminum ash is only about 40%, and the aluminum ash residue after disposal accounts for 50% of the total original aluminum ash, which is far from meeting the demand for resource reduction. In addition, the added value of the obtained residue is low, which is also the main factor restricting large-scale mass production. ④ High energy consumption: Although there is a combination of alkali sintering and Bayer process for aluminum ash in China, the energy consumption is high, the process is complex, the process is long, the investment is large, and the maintenance cost is high. The remaining residue is still about 30%. In practice, the products obtained by sintering (aluminum hydroxide, alumina) also face low economic benefits and fierce market competition.
[0004] Issues with waste sulfuric acid disposal include high treatment costs, high equipment investment, severe equipment corrosion, difficulty in secondary treatment, significant safety hazards, and high energy consumption. Commonly used processes for treating high-organic waste sulfuric acid include high-temperature pyrolysis, neutralization, and combined oxidation-adsorption. Key challenges in industrial implementation include: ① For waste sulfuric acid with high organic content, independent high-temperature pyrolysis requires sampling at temperatures of up to 1100°C, resulting in high energy consumption, high investment in sulfuric acid recovery equipment, and severe corrosion. ② Co-pyrolysis technologies, such as gypsum acid-to-cement units, require temperatures exceeding 1350°C, resulting in low added value calcium sulfate. Market supply far exceeds demand, resulting in poor economic returns and difficulties in sustainable mass production. ③ Concentrated regeneration of waste sulfuric acid requires concentration, membrane separation, and decolorization, requiring high corrosion resistance. However, the difficulties in decolorizing and removing organic matter from sulfuric acid often result in the subsequent sulfate product quality failing to meet market demand, hindering sustainable mass production. ④ Carbonization reduction technology, suitable for waste sulfuric acid generated in the petrochemical industry, is limited in the types of treatment options available and cannot meet the diverse needs of industrial waste sulfuric acid disposal.
[0005] Regarding accelerators, their actual use faces several drawbacks: ① The competitiveness of accelerators currently depends on their water content, which restricts transportation distances. ② Alkaline accelerators suffer from severe strength reduction, the risk of alkali-aggregate reaction, and corrosion of spraying equipment pipes. ③ The accelerator market is currently trending towards alkali-free accelerators, which are generally based on aluminum sulfate. The evaporated aluminum sulfate solid contains 48% water of crystallization, still exhibiting a high water content. ④ Anhydrous aluminum sulfate is difficult to obtain: The conventional process for preparing anhydrous aluminum sulfate involves first obtaining an aluminum sulfate solution and then evaporating and crystallizing it. However, due to its strong shrinkage, aluminum sulfate solids become fluid above 120°C, requiring temperatures above 300°C. Complete dehydration is difficult, making it difficult to achieve with equipment and resulting in high industrial energy consumption. ④ Energy waste: Anhydrous accelerators consume high energy during production, but still require the addition of an aqueous solution during use. While this saves transportation costs, the overall cost is still relatively high. Furthermore, energy is wasted throughout the entire production chain.
[0006] Existing patent CN113441510A discloses a landfill method for treating aluminum ash with industrial waste acid. The method proposes to treat industrial solid and liquid wastes by treating waste sulfuric acid and aluminum ash in a waste-to-waste manner, directly producing ammonium sulfate and aluminum ash slag. The patent fixes the harmful substance nitrogen with sulfuric acid, but does not address the treatment methods of harmful elements (fluorine, chlorine, hydrogen, salt, etc.) in aluminum ash and harmful substances (organic matter, salt, fluorine, etc.) in waste sulfuric acid, especially the safety hazards generated by hydrogen in the process and the environmental problem of odor. In addition, the process scheme does not realize the utilization of useful components in aluminum ash, adopts a landfill method, does not solve the problem of utilizing the resource value of aluminum ash, has poor economic benefits, cannot sustain industrial operation, and is difficult to achieve reduction, resource utilization, sustainability and feasibility in industrial implementation.
[0007] Existing patent CN118005061A discloses a method for preparing a highly active polyaluminum sulfate flocculant using secondary aluminum ash. The method includes mixing a phosphoric acid solution and a sulfuric acid solution, adding the solution to the secondary aluminum ash, stirring, drying, and calcining at 300-600°C. The resulting calcined activated material is then watered, stirred, and solid-liquid separated. A sodium hydroxide solution is then added to the liquid to adjust the pH to 3-6. The liquid is then irradiated with low-temperature plasma and dried to obtain a highly active polyaluminum sulfate flocculant. This process does not address methods for treating harmful substances such as nitrogen, salt, and fluorine in the aluminum ash, nor does it mention the safety risks of hydrogen generated during mixing. The product is polyaluminum sulfate, and the patent does not explain the role and fate of phosphoric acid. The slurry has a high moisture content, resulting in high energy consumption. Sodium hydroxide is used in the subsequent dissolution process to adjust the pH to 3-6, but the impact of pH on product quality is not addressed. This process does not consider the conversion of nitrogen from aluminum nitride, a harmful substance in the aluminum ash, into ammonium ions. The ammonia nitrogen content directly affects the quality of the aluminum sulfate flocculant and is a key control indicator. Furthermore, the aluminum ash contains approximately 10% salt, which also affects product quality.
[0008] Existing patent CN114477827A discloses a method for producing cement accelerators through the comprehensive treatment of secondary aluminum ash. The method involves mixing secondary aluminum ash, a calcium source, and an alkaline additive to obtain a mixed raw material. The mixture is calcined at 950-1200°C and cooled to produce the cement accelerator. The secondary aluminum ash contains 10% chloride salt, but the accelerator requires less than 0.1% chloride ions. Chloride is severely corrosive to steel, and the patent does not address this issue. Under alkaline conditions, the aluminum ash and calcium source undergo a side reaction, sintering to form calcium aluminate powder and agglomerating. Sodium metaaluminate is the catalyst for the accelerator, affecting the aluminum oxide extraction rate and the effectiveness of the accelerator. Currently, market demand for alkali-free accelerators is shifting from traditional alkaline accelerators to cost-effective alkali-free accelerators, but market demand is low. High alkali content can easily lead to concrete expansion and damage, generating corrosive dust that threatens the health of construction workers and can pollute the environment during production. Liquid accelerators, due to their inherent properties, have high transportation costs, limiting their market reach.
[0009] The above methods all propose methods of recovering aluminum oxide from aluminum ash using acid and alkali methods. None of them considers how to comprehensively utilize ammonia and hydrogen as parameters in the process, nor does it provide a final safe treatment method for chlorides and fluorides. The resulting products are of poor quality and high cost, and their market application scenarios are limited. Summary of the Invention
[0010] In response to the technical problems existing in the above-mentioned ZZ, the present invention proposes a process for preparing powdered anhydrous accelerating setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash, which has a reasonable design, can realize synergistic disposal, resource utilization, is environmentally friendly, has a stable process and has diversified products.
[0011] In order to achieve the above object, the technical solution adopted by the present invention is to provide a process for preparing a powdered anhydrous accelerating setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash, comprising the following specific steps: S1. Aluminum extraction from aluminum ash: The secondary aluminum ash is screened, separated and air-selected to obtain high-content aluminum ash; the high-content aluminum ash is ball-milled to obtain aluminum balls or aluminum flakes, and fine aluminum ash is separated. The aluminum content of fine aluminum ash is less than 1%, which can reduce the amount of hydrogen generated from the source and increase the feeding speed by 4-5 times; S2, denitrification and desalination: The aluminum ash treated in step S1 is hydrolyzed in a hydrolysis tank to perform denitrification and desalination, and harmless aluminum ash is obtained after washing; S3. Acidity adjustment of waste sulfuric acid: If the organic waste sulfuric acid is lower than 70%, use concentrated waste sulfuric acid or industrial sulfuric acid with a concentration greater than 98% to adjust the acidity of the low-concentration waste sulfuric acid to ensure that the concentration of the waste sulfuric acid participating in the reaction is greater than 70%; S4, high-temperature calcination and reaction: harmless aluminum ash and sulfuric acid are sprayed into a rotary kiln at a calcination temperature of 600-700°C. Under high temperature conditions, waste sulfuric acid reacts with aluminum oxide in the harmless aluminum ash to form aluminum sulfate. Metal oxides other than aluminum oxide in the harmless aluminum ash react with sulfuric acid to form corresponding sulfates, including magnesium sulfate and iron sulfate. Fluorine and aluminum in the harmless aluminum ash react at high temperature to form fluoride salts. The calcined clinker enters a cooling drum for cooling. S5, calcination waste gas treatment: the waste gas generated in step S4 is input into the waste gas system and converted into salt products through multi-stage absorption and adsorption treatment, the salt products including sulfate and sulfite; S6. Preparing an anhydrous accelerating setting admixture: adding an additive A according to the proportion of each component to the clinker obtained in step S4, wherein the clinker comprises aluminum sulfate, magnesium sulfate, ferric sulfate, and fluoride, wherein the additive A comprises at least sodium fluorosilicate and magnesium sulfate, and mixing the clinker and the additive A in a mixer to obtain an anhydrous accelerating setting admixture.
[0012] Preferably, before step S3, the aluminum ash is pretreated, and then the harmless aluminum ash and waste sulfuric acid can be used to quickly react to generate aluminum sulfate; the waste sulfuric acid contains organic matter, and the organic matter is fully burned in the rotary kiln. The combustion process releases a large amount of reaction heat, which can realize the energy conversion of organic matter and ensure the anhydration of the accelerating setting agent.
[0013] Preferably, in step S3, the organic waste sulfuric acid is first pretreated by using solid slag capable of adsorbing organic matter to remove part of the organic matter contained in the organic waste sulfuric acid.
[0014] Preferably, the adsorbable organic solid residue is pressed into a cake-shaped structure by a press as an organic adsorbent component.
[0015] Preferably, the organic adsorbent assembly includes a plurality of adsorption cam rings nested inside and outside, the inner hole of the adsorption cam ring is an eccentric hole, the bottom of the outer wall of the adsorption cam ring is provided with an annular groove, and the bottom of the inner hole of the adsorption cam ring is provided with a positioning ring platform.
[0016] Preferably, the adsorption cam ring includes two symmetrically arranged half rings, and the half ring is provided with two lifting blind holes near its distal end, and the lifting blind holes are symmetrically arranged on the upper surface and the lower surface of the half ring.
[0017] Preferably, the upper surface and the lower surface of the adsorption cam ring located on the outermost circle are provided with a plurality of conical holes distributed in a circular array, and the conical holes are used to install positioning rollers, and the positioning rollers are of a double-conical structure.
[0018] Preferably, a support is provided at the bottom of the organic adsorbent assembly, the support is a trough-shaped structure with an opening facing downward, a plurality of filter holes are provided on the surface of the support, and a plurality of radially distributed reinforcing ribs are provided inside the support. Compared with the prior art, the advantages and positive effects of the present invention are: The present invention provides a process for preparing a powdered anhydrous accelerating setting agent by synergistically processing organic waste sulfuric acid and aluminum ash. This process solves the problem of separate disposal of waste sulfuric acid and aluminum ash. Through the synergistic treatment of waste sulfuric acid and aluminum ash, the waste is converted into a marketable concrete admixture product. This process also significantly improves the recovery of organic matter from waste sulfuric acid, achieves more efficient reduction, and maximizes zero emissions, resulting in significant economic and environmental benefits. The present invention is rationally designed and can achieve synergistic disposal, resource utilization, energy recovery, environmental friendliness, stable process, high economic benefits, and product diversification, making it suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0020] Figure 1 A process diagram for preparing a powdered anhydrous quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash provided in Examples 1-5; Figure 2 A three-dimensional diagram of the organic adsorbent assembly provided by the present invention; Figure 3 A three-dimensional diagram of the organic adsorbent assembly provided by the present invention in another direction; Figure 4 A three-dimensional diagram of the organic adsorbent assembly and the support member provided by the present invention; Figure 5 A top view of the organic adsorbent assembly and support provided by the present invention; Figure 6 A bottom view of the organic adsorbent assembly and support provided by the present invention; In the above figures: 1. Organic matter adsorbent assembly; 2. Adsorption cam ring; 21. Eccentric hole; 22. Annular sink; 23. Positioning ring platform; 24. Half ring; 25. Lifting blind hole; 26. Conical hole; 3. Positioning roller; 4. Support; 41. Filter hole; 42. Reinforcement rib plate. DETAILED DESCRIPTION
[0021] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is further described below with reference to the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features therein can be combined with each other unless they conflict. For the convenience of description, the words "upper", "lower", "left", and "right" appearing below only indicate the upper, lower, left, and right directions consistent with the drawings themselves and do not limit the structure.
[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0023] The aluminum ash used in the following examples is secondary aluminum ash produced from an aluminum alloy casting process, and its elemental composition by mass is 70% Al2O3 (elemental aluminum, aluminum nitride, aluminum carbide, and other aluminum compounds, converted as alumina), 3.5% SiO2, 0.5% FeOx, 4.8% Mg, 0.5% Ca, 6% salt, 5.28% nitrogen, 1.6% F, and 0.6% carbon powder. The waste sulfuric acid is hazardous solid waste generated by chemical industries such as alkylated sulfuric acid, sulfonated sulfuric acid, dehydrated sulfuric acid, and catalyst sulfuric acid. Example 1
[0024] like Figure 1 As shown, the present invention provides a process for preparing a powdered anhydrous quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash, comprising the following specific steps: S1. Aluminum extraction from aluminum ash: 71% of aluminum oxide is screened, separated and air-selected to obtain high-content aluminum ash; the high-content aluminum ash is ball-milled to obtain aluminum balls or aluminum flakes, and fine aluminum ash is separated. The aluminum content of fine aluminum ash is less than 1%, which can reduce the amount of hydrogen generated from the source and increase the feeding speed by 4-5 times; S2, Denitrification and Desalination: The fine aluminum ash obtained in S1 is hydrolyzed with water in a hydrolysis tank at a liquid-to-solid ratio of 3:1. The temperature is controlled at 95°C-100°C, aeration is added simultaneously, and the liquid level is monitored during the process to prevent boiling. The reaction time is 8 hours. The ammonia released during the process is absorbed by tertiary sulfuric acid to produce ammonium sulfate; the hydrogen released during the process enters a high-temperature rotary kiln for combustion; the slurry after the reaction is separated into solid and liquid by a filter press, and the filter cake is filtered, washed, and air-dried to obtain a nitrogen content of <0.15%, a chlorine content of <0.1%, and an aluminum content of <0.1%, thereby obtaining a denitrified and desalted harmless aluminum ash; S3. Acidity adjustment of waste sulfuric acid: If the organic waste sulfuric acid is lower than 70%, use concentrated waste sulfuric acid (≥85%) or industrial sulfuric acid (concentration>98%) to adjust the acidity of the low-concentration waste sulfuric acid to ensure that the concentration of the waste sulfuric acid participating in the reaction is greater than 70%; S4. High-temperature calcination and reaction: The prepared waste sulfuric acid and harmless aluminum ash are sprayed into the rotary kiln at a mass ratio of 2.2:1 (sulfuric acid is converted to 98%), and the calcination temperature is 600-700°C for 30 minutes. During the high temperature process, the sulfuric acid and the metal oxides in the harmless aluminum ash react rapidly to produce sulfates and fluorides such as aluminum sulfate, magnesium sulfate, iron sulfate, and calcium sulfate. In the rotary kiln, the organic matter in the waste sulfuric acid can be fully burned to remove the organic matter. The combustion process releases a large amount of reaction heat, which can realize the energy conversion of the organic matter and also helps to ensure the dehydration of the accelerating setting agent. The calcined clinker is cooled in the cooling drum by air cooling. The clinker obtained from step S4 comprises: 72.7% aluminum sulfate, 8.3% magnesium sulfate, 0.35% iron sulfate, 3.88% sodium fluoride, and 1.5% other sulfates; 0.01% chloride; and 12.4% insoluble slag as a filler, the main component of which is corundum-grade alumina. S5. Calcination waste gas treatment: The waste gas generated in step S4 is fed into the waste gas system, and the residual aluminum nitride is converted into nitrogen at high temperature. The tail gas is converted into salt products through multi-stage absorption and adsorption treatment, and the salt products include sulfate and sulfite. The multi-stage absorption and adsorption treatment includes cyclone dust removal + pulse dust removal + water spraying + adsorption treatment, and the tail gas meets the emission standards; The effect of the accelerator on the clinker was tested: initial setting time 5'20s, final setting time 15'31s, compressive strength at 1 day old 5.0, compressive strength at 28 days old 61. Example 2
[0025] The modified condition of Example 2 is that the solid-liquid ratio of the waste acid and the harmless aluminum ash in step S4 is 2.3:1. Other than this, the rest of the process is the same as that of Example 1. The clinker obtained from step S4 in this embodiment comprises: 78.2% aluminum sulfate, 8.2% magnesium sulfate, 0.37% iron sulfate, 3.9% sodium fluoride, and 2% other sulfates; a chloride content of 0.01%; and 7% insoluble slag as a filler, the main component of which is corundum-grade alumina.
[0026] The effect of the accelerator on the clinker was tested: initial setting time 4'34s, final setting time 12'28s, compressive strength at 1d age 7.5, compressive strength at 28d age 83; the obtained powdered anhydrous accelerator was qualified. Example 3
[0027] The changed condition of Example 3 is that the solid-liquid ratio of the waste acid and the harmless aluminum ash in step S4 is 2.35:1. Other than this, the rest of the process is the same as that of Example 1.
[0028] The clinker obtained in this embodiment has the following composition: 82.4% aluminum sulfate, 7.6% magnesium sulfate, 0.4% iron sulfate, 3.6% sodium fluoride, and 2% other sulfates; 0.01% chloride; 5% insoluble slag as a filler, the main component of which is corundum-grade alumina; The effect of the accelerator on the clinker was tested: initial setting time was 3'04s, final setting time was 7'28s, compressive strength at 1d was 9.2, and compressive strength at 28d was 88; the obtained powdered anhydrous accelerator was qualified. Example 4
[0029] The changed condition of Example 4 is that the solid-liquid ratio of waste acid and harmless aluminum ash in step S4 is 2.4:1. Other than this, the rest of the process is the same as that of Example 1.
[0030] The obtained clinker composition is: 83.1% aluminum sulfate, 7.5% magnesium sulfate, 0.4% iron sulfate, 2.9% sodium fluoride, and 2% other sulfates; the chloride content is 0.01%; 4% insoluble slag is used as a filler, and the main component is corundum-grade alumina.
[0031] Add step S6 to prepare an anhydrous accelerating setting agent: condition the clinker, add additive A according to the proportion of each component, such as adding 2% sodium fluorosilicate, adjusting the magnesium sulfate content to 13%, and adding 1.5% white carbon black fine powder, and mix well to obtain a powdered anhydrous accelerating setting agent.
[0032] The test of the quick-setting agent effect: initial setting time 2'11s, final setting time 5'58s, 1-day compressive strength 11.7, 28-day compressive strength 92; the obtained powdered anhydrous quick-setting agent is a first-class product. Example 5
[0033] Example 5 changes the conditions to step S4 waste acid and harmless aluminum ash solid-liquid ratio of 2.45:1, except that the rest of the process is the same as Example 1. The clinker obtained in this embodiment comprises: 83.5% aluminum sulfate, 7.0% magnesium sulfate, 0.35% iron sulfate, 2.5% sodium fluoride, and 2% other sulfates; 0.01% chloride; 4.1% insoluble slag as a filler, and the main component is corundum-grade alumina.
[0034] Add step S6 to prepare an anhydrous accelerating setting agent: condition the clinker, add additive A according to the proportion of each component, such as adding 2% sodium fluorosilicate, adjusting the magnesium sulfate content to 15%, and adding 1.5% white carbon black fine powder, and mix well to obtain a powdered anhydrous accelerating setting agent.
[0035] The test of the quick-setting agent effect: initial setting time 2'04s, final setting time 4'28s, 1-day compressive strength 12, 28-day compressive strength 93; the obtained powdered anhydrous quick-setting agent is a first-class product.
[0036] The alkali-free powdered quick-setting materials prepared in Examples 1 to 5 were subjected to comparative tests. Portland cement, Shanshui Dongyue Testing of ordinary Portland cement for engineering use. The resulting alkali-free powdered accelerator was tested for setting time and mortar strength in accordance with GB / T35159-2017 "Accelerators for Shotcrete." The accelerator dosage was calculated as a percentage of cement weight. The test results are shown in the following table:
[0037] Furthermore, in step S3, the organic waste sulfuric acid is pretreated first. The pretreatment method is to use solid residue capable of adsorbing organic matter to remove part of the organic matter contained in the organic waste sulfuric acid.
[0038] Regarding adsorbable organic solid residue, the present invention prioritizes solid residue produced by alkylation waste sulfuric acid treatment. Since alkylation waste sulfuric acid contains 20% olefin polymers, it can be converted into carbonized polymers through a polymerization-addition reaction in the relevant process. This adsorbable organic solid residue is a carbonized polymer, primarily composed of high-molecular-weight hydrocarbons. Its structural foundation gives it adsorption properties distinct from those of conventional adsorbents, exhibiting a synergistic effect of physical adsorption and chemical adsorption: physical adsorption provides initial binding, while chemical adsorption enhances stability. More specifically, regarding physical adsorption, the carbonization process of the solid residue generates numerous pores with a high specific surface area, providing ample sites for adsorption. Furthermore, the multi-level pore distribution and the mesoporous structure of the carbonized polymer nanofibers accelerate the diffusion of organic matter from water to the adsorption sites. Regarding chemical adsorption, the carbonization process introduces oxygen- and nitrogen-containing functional groups, enhancing affinity for polar molecules through chemical adsorption. Therefore, the adsorbable organic solid residue, as a by-product of other processes, can be effectively utilized in this process and has good availability. It can not only be used in this process, but also can be used as an adsorption product in other process lines in the chemical industry.
[0039] In order to improve the adsorption performance of the solid residue capable of adsorbing organic matter as the organic matter adsorbent component 1 of the present invention, the solid residue provided by the present invention is pressed into a cake-shaped structure by a press.
[0040] Furthermore, the provided organic adsorbent assembly 1 includes a plurality of adsorption cam rings 2 nested in an inner and outer arrangement. The inner hole of each adsorption cam ring 2 is an eccentric hole 21. The bottom of the outer wall of each adsorption cam ring 2 is provided with an annular groove 22. The bottom of the inner hole of each adsorption cam ring 2 is provided with a positioning ring platform 23. The outer ring of each adsorption cam ring 2 is a perfect circle, and the inner ring is an eccentric hole 21. The eccentric hole 21 of each adsorption cam ring 2 is used to mount an adsorption cam ring 2 one level smaller than the adsorption cam ring. The cooperating annular grooves 22 and positioning ring platforms 23 form a mutual support. At the same time, the bottom of the largest adsorption cam ring 2 may not be provided with an annular groove 22, and the bottom of the smallest adsorption cam ring 2 may not be provided with a positioning ring platform 23. Moreover, the inner side of the smallest adsorption cam ring 2 remains hollow. The present invention presses solid slag into a cake-shaped structure with multiple voids, which, on the one hand, facilitates its installation in the adsorption treatment equipment; on the other hand, compared with bulk solid slag, the formed multi-void cake-shaped structure is beneficial to improving the uniformity of the treatment of waste sulfuric acid on a unit cross-section by the organic adsorbent assembly; furthermore, the use of a detachable adsorption cam ring 2 can achieve targeted replacement, which is beneficial to improving the utilization rate of the entire organic adsorbent assembly 1; the organic adsorbent assemblies 1 assembled in sequence from top to bottom, in addition to improving the treatment efficiency of organic matter carried by waste sulfuric acid by increasing the adsorption working surface, on the other hand, each layer of organic adsorbent assembly 1 uses an eccentric hole 21 as a mounting hole. By changing the relative angle of the organic adsorbent assemblies 1 of the adjacent layers, structural support can be provided for the organic adsorbent assembly 1 of the upper layer without affecting the rotation adjustment of other adsorption cam rings 2 on the same layer, thereby effectively ensuring the structural strength and stability of the entire organic adsorbent assembly 1 in the adsorption equipment, thereby better exerting the adsorption effect on organic matter in other high-organic waste sulfuric acid.
[0041] To facilitate assembly of the adsorption cam ring 2, the adsorption cam ring 2 provided herein includes two symmetrically arranged half-rings 24. Each half-ring 24 is provided with two blind hoisting holes 25 near its distal end. These blind hoisting holes 25 are symmetrically located on the upper and lower surfaces of the half-rings 24. This allows the pair of half-rings 24 to be assembled into the adsorption equipment sequentially. Furthermore, the curved inner wall of the eccentric hole 21 allows the half-rings 24 to pass through pipe openings smaller than their actual diameters, meeting the assembly requirements of adsorption cam rings 2 of varying diameters while preventing any harsh impacts that could affect their use. The blind hoisting holes 25 provided on the half-rings 24 can serve as hoisting nodes. Hoisting equipment in a workshop or factory can be used to clamp a hoisting fixture to the two blind hoisting holes 25, facilitating efficient installation of the adsorption cam ring 2 into the adsorption tank / tower. Furthermore, the blind hoisting holes 25 are located distally from the eccentric hole 21, i.e., at a larger solid surface, which helps ensure the quality of the adsorption cam ring 2 before and after installation.
[0042] In order to improve the overall stability of the organic adsorbent assembly 1, the present invention provides a plurality of conical holes 26 distributed in a circular array on the upper and lower surfaces of the adsorption cam ring 2 located in the outermost ring. The conical holes 26 are used to install positioning rollers 27. The positioning rollers 27 are of a double-conical structure, which facilitates their rapid mating and positioning with the upper and lower adsorption cam rings 2. By using the positioning rollers 27 and the conical holes 26 in combination, the upper and lower adjacent adsorption cam rings 2 can be positioned. In this way, the positions of the eccentric holes 21 of the upper and lower layers can be reasonably adjusted by manually assembling the adsorption cam rings 2 in a controllable manner, so that the adsorption cam rings 2 of the adjacent layers support each other. At the same time, for the smallest eccentric hole 21, a portion of the treated liquid can be accommodated inside it, and the resistance of the waste sulfuric acid passing through the surfaces of the adsorption cam rings 2 of different layers can be appropriately adjusted, which is conducive to improving the adsorption treatment efficiency.
[0043] To enhance the structural stability of the organic adsorbent assembly within the adsorption tank / tower, the present invention provides a support member 4 at its base. This support member 4 is a downward-facing, trough-shaped structure with a plurality of filter holes 41 formed on its surface and a plurality of radially distributed reinforcing ribs 42 disposed within it. The support member 4, with its reinforcing ribs 42, provides superior structural strength. The filter holes 41 on its surface allow for the passage of filtrate, while its grooved edges allow for engagement with the inner shoulder of the adsorption tank / tower. This support member 4 provides support for the organic adsorbent assembly 1, thereby ensuring its performance.
[0044] The above description is merely a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any person skilled in the art may utilize the technical contents disclosed above to change or modify them into equivalent embodiments with equivalent changes for application in other fields. However, any simple modification, equivalent change, and modification of the above embodiments made in accordance with the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A process for preparing powdered anhydrous accelerating setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash, characterized in that: The specific steps include: S1. Aluminum extraction from aluminum ash: The secondary aluminum ash is screened, separated and air-selected to obtain high-content aluminum ash; the high-content aluminum ash is ball-milled to obtain aluminum balls or aluminum flakes, and fine aluminum ash is separated. The aluminum content of fine aluminum ash is less than 1%, which can reduce the amount of hydrogen generated from the source and increase the feeding speed by 4-5 times; S2, denitrification and desalination: The aluminum ash treated in step S1 is hydrolyzed in a hydrolysis tank to perform denitrification and desalination, and harmless aluminum ash is obtained after washing; S3. Acidity adjustment of waste sulfuric acid: If the organic waste sulfuric acid is lower than 70%, use concentrated waste sulfuric acid or industrial sulfuric acid with a concentration greater than 98% to adjust the acidity of the low-concentration waste sulfuric acid to ensure that the concentration of the waste sulfuric acid participating in the reaction is greater than 70%; S4, high-temperature calcination and reaction: harmless aluminum ash and sulfuric acid are sprayed into a rotary kiln at a calcination temperature of 600-700°C. Under high temperature conditions, waste sulfuric acid reacts with aluminum oxide in the harmless aluminum ash to form aluminum sulfate. Metal oxides other than aluminum oxide in the harmless aluminum ash react with sulfuric acid to form corresponding sulfates, including magnesium sulfate and iron sulfate. Fluorine and aluminum in the harmless aluminum ash react at high temperature to form fluoride salts. The calcined clinker enters a cooling drum for cooling. S5, calcination waste gas treatment: the waste gas generated in step S4 is input into the waste gas system and converted into salt products through multi-stage absorption and adsorption treatment, the salt products including sulfate and sulfite; S6. Preparing an anhydrous accelerating setting admixture: adding an additive A according to the proportion of each component to the clinker obtained in step S4, wherein the clinker comprises aluminum sulfate, magnesium sulfate, ferric sulfate, and fluoride, wherein the additive A comprises at least sodium fluorosilicate and magnesium sulfate, and mixing the clinker and the additive A in a mixer to obtain an anhydrous accelerating setting admixture.
2. The process for preparing anhydrous powdered quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 1, characterized in that: Before step S3, the aluminum ash is pretreated, and then the harmless aluminum ash and waste sulfuric acid can be quickly reacted to generate aluminum sulfate; the waste sulfuric acid contains organic matter, and the organic matter is fully burned in the rotary kiln. The combustion process releases a large amount of reaction heat, which can realize the energy conversion of organic matter and ensure the anhydration of the accelerating setting agent.
3. The process for preparing anhydrous powdered quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 1, characterized in that: In step S3, the organic waste sulfuric acid is first pretreated. The pretreatment method is to use solid residue capable of adsorbing organic matter to remove part of the organic matter contained in the organic waste sulfuric acid.
4. The process for preparing anhydrous powdered quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 3, characterized in that: The organic matter adsorbable solid residue is pressed into a cake-shaped structure as an organic matter adsorbent component by a press.
5. The process for preparing powdered anhydrous accelerating setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 4, characterized in that: The organic matter adsorbent assembly includes a plurality of adsorption cam rings nested inside and outside, the inner hole of the adsorption cam ring is an eccentric hole, the bottom of the outer wall of the adsorption cam ring is provided with an annular groove, and the bottom of the inner hole of the adsorption cam ring is provided with a positioning ring platform.
6. The process for preparing powdered anhydrous accelerating setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 5, characterized in that: The adsorption cam ring includes two symmetrically arranged half rings, and the half ring is provided with two lifting blind holes near its distal end. The lifting blind holes are symmetrically arranged on the upper surface and the lower surface of the half ring.
7. The process for preparing anhydrous powdered quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 6, characterized in that: The upper surface and lower surface of the adsorption cam ring located on the outermost circle are provided with a plurality of conical holes distributed in a circular array, and the conical holes are used to install positioning rollers, and the positioning rollers are of a double-conical structure.
8. The process for preparing anhydrous powdered quick-setting agent by synergistic resource treatment of organic waste sulfuric acid and aluminum ash according to claim 7, characterized in that: A support member is provided at the bottom of the organic adsorbent assembly. The support member is a trough-shaped structure with an opening facing downward. A plurality of filter holes are provided on the surface of the support member. A plurality of radially distributed reinforcing ribs are provided inside the support member.
Citation Information
Patent Citations
Technological method for producing accelerator and flocculant by using aluminum ash
CN109369053A
Liquid alkali-free accelerator as well as preparation method and application thereof
CN113480226A
Low-temperature harmless wet treatment method for aluminum ash
CN114032396A
Preparation method and application of high-performance powdery alkali-free accelerator core master batch
CN119161125A
Cooperative treatment method for secondary aluminum ash and overhaul slag
CN120004301A
Cited By
Treatment process for preparing microporous carbon from waste sulfuric acid
CN121180974A